BS EN 60670-24 AMD1. Boxes and enclosures for electrical accessories for household and similar fixed electrical installations. Part 24. Particular requirements for enclosures for housing protective devices and other power dissipating electrical equipment (19th August 2021) - British Standards Institution,
No abstract available